A Multilevel Intervention to Identify Individuals for Genetic Testing and Treatment - Kirsten A. Jorgensen; Nuria Agusti; Tara Coffin; Karla Barajas; Maria D. Iniesta; Erica M. Bednar; Alexa Kanbergs; Roni Nitecki Wilke; Isabel Beshar; Sara Pirzadeh-Miller; Sayoni Lahiri; Kathy Pratt; et al. (JAMA Network Open, 2026)
Importance Cascade genetic testing (CGT) is a key strategy for cancer prevention in families with hereditary breast and ovarian cancer syndrome (HBOC) and Lynch syndrome (LS), yet uptake among at-risk relatives remains persistently low, particularly in medically underserved populations where structural and informational barriers limit access to genetic services. Objective To evaluate the feasibility and preliminary effects of IGNITE-TX (Identifying Individuals for Genetic Testing and Treatment), a scalable, bilingual, navigator-supported digital intervention designed to increase CGT uptake among at-risk relatives of individuals with HBOC or LS. Design, Setting, and Participants In this 2 × 2 factorial pilot randomized clinical trial, probands with HBOC or LS self-enrolled online from October 1, 2023, to February 15, 2025, after recruitment through clinical, laboratory, and community pathways across the US and invited their at-risk relatives to participate. Families were cluster-randomized to 4 study arms (1:1:1:1); outcomes were assessed at 6 months. Interventions Usual care with standard printed materials (arm 1); no-cost telegenetic counseling and testing, self-initiated by the at-risk relative (arm 2); IGNITE-TX, comprising proactive family genetic navigator support and access to a bilingual digital education and decision-support platform (arm 3); or IGNITE-TX plus no-cost telegenetic counseling and testing with navigator-assisted access (arm 4). Main Outcomes and Measures Feasibility outcomes were enrollment and survey completion at baseline and 6 months. Secondary outcomes were CGT completion among at-risk relatives, informed decision-making, and readiness along the genetic testing pathway. Results In this pilot randomized clinical trial, 60 probands (median age, 46.5 [range, 20-83] years; 59 female [98.3%]) and 144 at-risk relatives (median age, 39 [range, 18-87] years; 71 female [49.3%]) were enrolled. Among at-risk relatives, 99 (68.8%) reported at least 1 structural barrier to care. A total of 58 probands (97.2%) and 117 at-risk relatives (81.3%) completed the 6-month survey. Among at-risk relatives, 1 of 29 (3.4%) completed CGT in arm 1, 8 of 39 (20.5%) in arm 2, 17 of 30 (56.7%) in arm 3, and 36 of 46 (78.3%) in arm 4. Compared with non–IGNITE-TX arms, at-risk relatives in IGNITE-TX arms showed greater CGT completion (odds ratio, 26.9; 95% CI, 2.4-59.5), informed decision-making (48 of 60 [80.0%] vs 8 of 57 [14.0%]; P < .001), and readiness to pursue CGT (action stage: 53 of 61 [86.9%] vs 9 of 55 [16.4%]; P < .001). Conclusions and Relevance In this pilot randomized clinical trial, IGNITE-TX was feasible to deliver in a community-recruited cohort with structural barriers to care and was associated with higher CGT completion and improved informed decision-making and readiness compared with non–IGNITE-TX arms. These findings support further evaluation of IGNITE-TX as a scalable navigation model for equitable hereditary cancer care. Trial Registration ClinicalTrials.gov Identifier: NCT05677048